Pressure-Driven Opening and Filling of a Volcanic Hydrofracture Recorded by Tuffisite at Húsafell, Iceland: A Potential Seismic Source - Unwin, Holly E.; Tuffen, Hugh; Phillips, Emrys; Wadsworth, Fabian B.; James, Mike R. (Frontiers in Earth Science, 2021)
The opening of magmatic hydraulic fractures is an integral part of magma ascent, the triggering of volcano seismicity, and defusing the explosivity of ongoing eruptions via outgassing magmatic volatiles. If filled with pyroclastic particles, these fractures can be recorded as tuffisites. Tuffisites are therefore thought to play a key role in both initiating eruptions and controlling their dynamics, and yet their genesis remains poorly understood. Here we characterise the processes, pressures and timescales involved in tuffisite evolution within the country rock through analysis of the sedimentary facies and structures of a large sub-horizontal tuffisite vein, 0.9 m thick and minimum 40 m in length, at the dissected Húsafell volcano, western Iceland. The vein occurs where a propagating rhyolitic sheet intrusion stalled at a depth of ∼500 m beneath a relatively strong layer of welded ignimbrite. Laminations, cross-stratification, channels, and internal injections indicate erosion and deposition in multiple fluid pulses, controlled by fluctuations in local fluid pressure and changes in fluid-particle concentration. The field evidence suggests that this tuffisite was emplaced by as many as twenty pulses, depositing sedimentary units with varying characteristics. Assuming that each sedimentary unit (∼0.1 m thick and minimum 40 m in length) is emplaced by a single fluid pulse, we estimate fluid overpressures of ∼1.9–3.3 MPa would be required to emplace each unit. The Húsafell tuffisite records the repeated injection of an ash-laden fluid within an extensive subhorizontal fracture, and may therefore represent the fossil record of a low-frequency seismic swarm associated with fracture propagation and reactivation. The particles within the tuffisite cool and compact through time, causing the rheology of the tuffisite fill to evolve and influencing the nature of the structures being formed as new material is injected during subsequent fluid pulses. As this new material is emplaced, the deformation style of the surrounding tuffisite is strongly dependent on its evolving rheology, which will also control the evolution of pressure and the system permeability. Interpreting tuffisites as the fossil record of fluid-driven hydrofracture opening and evolution can place new constraints on the cycles of pressurisation and outgassing that accompany the opening of magmatic pathways, key to improving interpretations of volcanic unrest and hazard forecasting.